The Brain-based Model and the Habits of Mind to enhance future teachers’ linguistic-communicative competence - Cappuccio, Giuseppa; Compagno, Giuseppa (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
The alternation, within the national scientific debate, between Neuroeducation research and the related theories on the mind, may be applied to different disciplinary areas with the aim of an overall implementation of the teaching/learning process. Language teaching approaches such the Brain-based ones, with particular reference to ‘Brain-gym’ (Mac Lean, 1975, Dennison, 2008) and educational activities aimed at developing the Habits of Mind (Costa - Kallick, 2008) are the keynotes of the research, here described, carried out with 205 students attending the 2nd year of the degree course in Primary Education from the University of Palermo in A.Y. 2015-2016. Through the research process we wanted to verify the validity of the Brain-based model in order to reinforce in students the linguistic, pragmatic communicative, and strategic skills both in the broad sense and with respect to the specific research subject areas covered.